2011
DOI: 10.1039/c1dt11020a
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the reactions of tripodal pyridine-containing ligands with Re(CO)5Br leading to rheniumtricarbonyl complexes with potential biomedical applications

Abstract: The complexes formed from the reaction of N-acylated tris-(pyridin-2-yl)methylamine (LH) with [Re(CO)(5)Br] depend on the structure of the ligand and the reaction conditions. Thus, while N-[1,1,1-tris-(pyridin-2-yl)methyl]acetamide coordinates through the three pyridine nitrogens to give a stable cationic complex [LHRe(CO)(3)Br], the analogous N-benzoyl ligand reacts under similar conditions to give a neutral complex [LRe(CO)(3)] with coordination through two pyridine nitrogens and a deprotonated amide. To try… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…31 The dinuclear nature of the initial product of the transformation, 7a, has been confirmed crystallographically. However, we have also now shown that aqueous solutions of 7a react further, forming mononuclear copper/carbonato (8) and ligand disproportionation products (9).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…31 The dinuclear nature of the initial product of the transformation, 7a, has been confirmed crystallographically. However, we have also now shown that aqueous solutions of 7a react further, forming mononuclear copper/carbonato (8) and ligand disproportionation products (9).…”
Section: Discussionmentioning
confidence: 68%
“…Tris-( pyrid-2-yl)methane, tris-( pyrid-2-yl)amine, tris-( pyrid-2yl)phosphine and related compounds were first synthesised in the first half of the 20 th century, 1 and developed as tripodal ligands for transition ions in the 1960-1980s. [2][3][4] Despite this long-standing chemistry, they continue to find use as facial protecting groups in organometallic chemistry, [5][6][7] catalysis, 8 transition metal photochemistry, 9 molecular magnetism [10][11][12][13][14] and other aspects of coordination chemistry. 15 A number of such ligands py 3 X ( py = 2-pyridyl) have been prepared, with different bridgehead groups 'X' (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…1, 1) ligand families are the most commonly exploited tridentate scaffolds. However, ligands that contain thiazolyl, 6 pyridyl, 9,10 pyrazolyl, 11 imidazolyl, 10,12 Fig. 1 The ubiquitous biofunctionalised tridentate ligands, bis (2methylpyridyl)amine or 2-[bis (2-methylquinolinyl)]amine 1, and the related tridentate "click" ligand 2,6-bis(4-substituted-1,2,3-triazol-1ylmethyl)pyridine, 2. benzoimidazolyl, 7 and even "click" derived 1,2,3-triazoyl 12,13 heterocyclic units have all been synthesised and characterised.…”
Section: Introductionmentioning
confidence: 99%
“…1A). [1][2][3] The conjugate base carboxamidates can bind through oxygen or nitrogen as well (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%